Wirtschaftsgeographische Probleme der Industrieansiedlung in den neuen Entlastungsstädten der ägyptischen Metropole - Meyer, Günter (ERDKUNDE, 1988)
Three new satellite cities are at present under construction in desert areas near Cairo. In each of these New Towns, which are designed for 500000 inhabitants, up to 80 000 jobs in industry are to be created before the year 2000. Altogether 229 manufacturing enterprises with a labour force of more than 17 000 people had started production by the end of 1986. A survey of these firms revealed the predominance of capital-intensive enterprises most of which produce consumer goods for the domestic market and depend largely on imported inputs. The entrepreneurs' main reasons for choosing the satellite cities as the location for their new factories were the good infrastructure, the low price of land, tax reductions, and other incentives offered by the government. Before setting up their factory in the new cities one out of three entrepreneurs had already owned a factory in Cairo. Other important groups of entrepreneurs are traders, former labour emigrants, native engineers and foreign companies. The impact of Islamic investment groups is rising dramatically. So far, the overwhelming majority of the labour force has to be transported every day from the centre of Cairo and from neighbouring localities in the Nile Delta to the new factories and back. In general, the latest industrial expansion in the new cities in Egypt has to be regarded as a successful example of industrial decentralization in developing countries.